Influence characteristics inpatients to satisfaction services at Regional Hospital Konawe Selatan, Indonesia - Iva Tria; I Made Christian Binekada (Yayasan Cipta Anak Bangsa (YCAB) Publisher, 2024)
Background: The South Konawe Regional Hospital (RH) plays a crucial role in providing healthcare services to the community. Established under Law Number 30 of 2019, the hospital is committed to continuously improving service quality. Over the past three years, RH Konawe Selatan has focused on enhancing the quality of its inpatient care services. Objective: This study aims to analyze the impact of patient characteristics on service satisfaction at RH Konawe Selatan in 2021. Methods: The study population included all inpatients at RH Konawe Selatan from January to May 2021, totaling 1,634 patients. A sample of 94 patients was selected for the study. Data were analyzed using chi-square tests, which are comparative and parametric tests that do not require normal data distribution. Results: The study found significant effects of age (p = 0.000, p < 0.05), gender (p = 0.007, p < 0.05), education (p = 0.000, p < 0.05), occupation (p = 0.001, p < 0.05), and income (p = 0.001, p < 0.05) on the evaluation of service quality in the inpatient ward of South Konawe Regional Hospital. Keywords: patient characteristics; patient satisfaction; service quality; hospital